2013
DOI: 10.5194/hess-17-3261-2013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glacial meltwater runoff in a karstic environment and its implication for present and future water availability

Abstract: Abstract. Glaciers all over the world are expected to continue to retreat due to the global warming throughout the 21st century. Consequently, future seasonal water availability might become scarce once glacier areas have declined below a certain threshold affecting future water management strategies. Particular attention should be paid to glaciers located in a karstic environment, as parts of the meltwater can be drained by underlying karst systems, making it difficult to assess water availability. In this st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 43 publications
1
47
0
1
Order By: Relevance
“…In terms of the studied region, due to similar climatic conditions, it is also possible to acknowledge the accuracy of statements (Finger et al, 2013) that the main natural factors of forming mountain rivers' runoffs, including the maximal meltwater runoff, are the vertical zonation of the climate and its change from the West to the East. This allows determining the local dependences of maximal meltwater runoff rates on the average height of basins, and using them to estimate this runoff for unstudied rivers.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the studied region, due to similar climatic conditions, it is also possible to acknowledge the accuracy of statements (Finger et al, 2013) that the main natural factors of forming mountain rivers' runoffs, including the maximal meltwater runoff, are the vertical zonation of the climate and its change from the West to the East. This allows determining the local dependences of maximal meltwater runoff rates on the average height of basins, and using them to estimate this runoff for unstudied rivers.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…As an alternative method of estimating the maximal meltwater runoff, it is possible to use its connection with the annual one, but with an obligatory inclusion of a second factor -the natural overregulation coefficient of the runoff, which depends on the size of the catchment basin (Finger et al, 2013).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have only been a few studies that have adequately evaluated the impact of predicted environmental changes on water quantity (e.g. Pinault et al 2005;Hartmann et al 2012;Finger et al 2013;Jia et al 2017).…”
Section: Karst Hydrogeologymentioning
confidence: 99%
“…Plaine Morte is the largest plateau glacier in the European Alps; almost its entire surface area shows no significant topographic gradients. Dye tracer experiments have shown that a considerable fraction of the meltwater is drained southwards to the Rhone Valley through subsurface conduits in the karstic system although the glacier surface is entirely located in the drainage basin of the Rhine River (Finger et al, 2013). A potential future change in the water supply due to glacier mass loss is a major concern in the summer-dry region around Crans-Montana, Valais, which is studied in the frame of the interdisciplinary project MontanAqua (Weingartner et al, 2010;Schneider and Homewood, 2013).…”
Section: Introductionmentioning
confidence: 99%